Sources of Pleistocene to Recent Alluvial Sediments of Northwestern Bilogora and Surrounding Areas (Croatia) (Rudarsko-geološko-naftni zbornik, 2025)
This study aims to determine the provenance of Pleistocene to recent alluvial sediments in the area of NW Bilogora. The research area includes Pannonian inselbergs of northern Croatia with a major focus on Bilogora Mountain. Framework composition and heavy mineral assemblages of sand samples, together with micropetrographical characteristics and whole-rock geochemistry of volcanic and volcaniclastic pebbles and rocks are used to explore sources of Lower-Middle Pleistocene deposits of the oldest Drava River terrace, along with local stream and river sediments. The development of this area is closely linked to local and regional tectonic processes, as well as the formation of the Drava-Mura River system which has supplied detrital material from the Eastern Alps, at least since Miocene times. The composition of Pleistocene sands points to extensive recycling from local Neogene sedimentary units, a process which is still ongoing today. Silicic pebbles correlate well with the widespread Permian-Triassic igneous activity in the Austroalpine units and Tisia, though the pebbles are likely recycled from Miocene conglomerates. Findings of mafic volcanic lithoclasts indicate the possibility of erosion of the pre-Neogene basement of mountains Kalnik and Ivanščica as well. During the Early-Middle Pleistocene, the Drava River basin of today’s northern Bilogora area received material from the Alps, along with local supply from units exposed on uplifting local inselbergs. Intermittent changes in sediment supply dynamics could have been affected by climatic changes and local uplift tectonics, coupled with hydrological dynamics in the Drava River during the Pleistocene.